The Confraternal Movement in Braga (Portugal) in the Sixteenth and Seventeenth Centuries: Devotion, Music, and Power - Lessa, Elisa (Confraternitas, 2020)
The confraternal movement in Braga dates back to the early Middle Ages with the existence of at least two confraternities from that time: the Confraternity of São João do Souto (St John [the Baptist] of Souto), a parish in the diocese of Braga, documentation for which can be traced back to 1186; and that of the Santíssima Trindade (the Most Holy Trinity), founded in 1381 in Braga Cathedral. However, it was from the end of the sixteenth century and throughout the seventeenth century that confraternities developed most fully in this region of Portugal. This article aims to identify and analyze devotional celebrations through references to music in the statutes and regulations of the main confraternities and brotherhoods in Braga between the years 1500 and 1700. The festive celebrations of patronal feast days and other important feasts in the liturgical calendar will be discussed as practices of sociability and power in which the musical investment was of particular importance. The confraternities of São João do Souto and the Misericórdia in Braga are the focus of the contribution confraternities made to the urban soundscape.